Reproductive health among tactical athletes: an examination of physical activity and occupational concerns - Kehler, Ainslie Kathryn (Kansas State University, 2018)
Tactical athletes (e.g., law enforcement, military, firefighters) require a proportionate fitness level, along with specific technical and tactical skills, to achieve short-term objectives and disable various threats. Although these professions have unique job duties and workplace exposures, tactical athletes share many commonalities. A tactical athlete’s occupation requires her to be physically prepared for the unknown to protect the public. So what happens when the tactical athlete becomes pregnant? Benefits of physical activity throughout pregnancy for athletes, non-athletes, and baby have been well-documented. However, certain common tactical occupational conditions may result in adverse birth outcomes. These include shift work, high job stress, and exposures such as lead handling or high ambient temperatures. Additionally, extreme physical exertion around the implantation period may harm the developing embryo. In an unpredictable, potentially extremely physically demanding and stressful job environment, the pregnant tactical athlete may have higher risk for adverse birth outcomes compared to other women. The purpose of this dissertation was to examine the reproductive health of physically active females with specific focus on tactical athletes. First, we wanted to determine any exercise limits for pregnant athletes. We were also interested whether reproductive health was an important concern for this population, and if their adverse birth outcomes were higher compared to the United States national average. Chapter one reviews the literature, examining the female athlete and tactical athlete, the physical and occupational demands of tactical professions, and the reproductive health concerns among law enforcement officers (LEOs) and firefighters. Chapter two is a comprehensive review on prenatal exercise. It highlights the lack of scientific rigor presented in earlier guidelines, and states the need for more research on the upper limits of exercise intensity for athletes. Female athletes can usually maintain regular exercise training during pregnancy. Chapter three uses grounded-theory to investigate reproductive health concerns among firefighters. Results indicate that reproductive health is unquestionably a large concern, with four resulting themes (i.e., decision-making, recruitment and retention, policy variation, and lack of research). Chapter four investigates adverse reproductive health outcomes in female LEOs. Miscarriage rates are compared with a large prospective linkage study, preterm birth rates are compared to a large systematic US review study, and links are explored between specific job exposures and pregnancy loss. Miscarriage rate for our population are 19.1%, and preterm birth rates are 16.4%, both significantly higher than US averages. Physical activity, including strenuous occupational demands during pregnancy, is not associated with pregnancy loss among female LEOs. Chapter five presents a findings summary and future research directions. Miscarriage and preterm birth appear to be higher than average for both female firefighters and LEOs. Exercise did not play a large role in the concerns of female firefighters, or findings from female LEOs. Future research should be conducted specifically on females working in tactical occupations, with an emphasis on reproductive health concerns. More education should be provided at the organization level on the potential occupational exposures that can cause increased risk of adverse birth outcomes in female tactical athletes.
Keywords: Tactical athletes; First responders; Reproductive health; Occupational health; Miscarriage; Pregnancy